Human primary muscle stem cells regenerate injured urethral sphincter in athymic rats. Issue 5 (8th October 2022) - Bekele, Biniam M.; Schöwel‐Wolf, Verena; Kieshauer, Janine; Marg, Andreas; Busjahn, Andreas; Davis, Sarah; Nugent, Gayle; Ebert, Anne‐Karoline; Spuler, Simone
Abstract: Background: The aim of the study was to demonstrate the efficacy of human muscle stem cells (MuSCs) isolated using innovative technology in restoring internal urinary sphincter function in a preclinical animal model. Methods: Colonies of pure human MuSCs were obtained from muscle biopsy specimens. Athymic rats were subjected to internal urethral sphincter damage by electrocauterization. Five days after injury, 2 × 10 5 muscle stem cells or medium as control were injected into the area of sphincter damage ( n = 5 in each group). Peak bladder pressure and rise in pressure were chosen as outcome measures. To repeatedly obtain the necessary pressure values, telemetry sensors had been implanted into the rat bladders 10 days prior to injury. Results: There was a highly significant improvement in the ability to build up peak pressure as well as a pressure rise in animals that had received muscle stem cells as compared to control ( p = 0.007) 3 weeks after the cells had been injected. Only minimal histologic evidence of scarring was observed in treated rats. Conclusion: Primary human muscle stem cells obtained using innovative technology functionally restore internal urethral sphincter function after injury. Translation into use in clinical settings is foreseeable. Abstract : Human muscle stem cells repair injured urethral sphincter. Improvement in ability to build up bladder pressure and rise in pressure is seen after transplantation of cells compared to controls. Restoration of injured urethral sphincter is further supported by histologic examination.